Long-term outcomes of transcatheter aortic valve implantation: a single-center observational study - A. A. Baranov; A. G. Badoyan; D. A. Khelimsky; A. Yu. Tsydenova; Sh. Sh. Zainobidinov; V. A. Boboshko; O. V. Krestyaninov (Российский кардиологический журнал, 2025)
Aim. To evaluate remote outcomes of transcatheter aortic valve implantation (TAVI), including overall survival, freedom from cardiovascular death, permanent pacemaker implantation, and repeat valve replacement.Material and methods. This retrospective observational study included 535 patients who underwent TAVI from April 2015 to January 2024. Patients who underwent TAVI for moderate aortic stenosis or severe aortic valve regurgitation (n=35) were excluded from the analysis. A total of 500 patients were included in the final analysis. Males accounted for 40,8%. Most patients had intermediate EuroSCORE II risk (5,2%), as well as low STS-PROM score risk (2,9%). The median follow-up period was 2,2 (0,6;4,1) years.Results. Overall patient survival was 94%, 88%, 86%, and 58% at 1, 3, 5, and 8 years, respectively. Freedom from cardiovascular death was 97%, 90%, 78%, and 61% at 1, 3, 5, and 8 years, respectively. The cumulative freedom from permanent pacemaker implantation over the entire follow-up period was 89,4%, and from repeat pacemaker replacement — 98,8%. The factors influencing the long-term all-cause mortality were male sex, smoking, cancer, and left ventricular mass index. The only independent predictor of cardiovascular death was the STS-PROM score.Conclusion. Our experience demonstrates satisfactory long-term outcomes of transcatheter aortic valve implantation in patients with severe aortic stenosis in terms of overall survival, cardiovascular death, permanent pacemaker implantation, and repeat pacemaker replacement. Independent predictors of all-cause death were male sex, smoking, cancer, and left ventricular mass index. The only independent predictor of cardiovascular death in the long-term period was the STS-PROM score.